Mendeteksi Objek Bulat Secara Real-Time Menggunakan Model Warna HSV Berbasis Android - Hikmahwan, Bagus; Fu’adi, Anwar; Putra, Berlin Juliartha Martin; Nugroho, Berto Yusuf (Unit Penelitian, Pengabdian Kepada Masyarakat dan Penjamnan Mutu Akademi Komunitas Negeri Pacitan, 2024)
An object has distinct characteristics, particularly in terms of shape and color. The use of color in object measurement is common but still has drawbacks, especially if the object is not exposed to sufficient lighting, which can reduce accuracy. In detecting circular objects, we can utilize HSV color elements and the object's shape to measure its roundness. Roundness is a crucial characteristic in various applications such as manufacturing, agriculture, and medical technology. However, accurate and fast roundness measurement often requires specialized, expensive, and complex equipment. This research uses image processing technology and color analysis to address these challenges. We developed an Android-based application that utilizes the commonly used smartphone camera to identify objects based on color changes along the object's contour. To detect roundness, we also use the Circle Hough Transform, which is frequently employed to efficiently detect round objects. Measurements are performed in real-time, allowing users to obtain results quickly and accurately. Testing results show that this method can provide consistent and relatively accurate outcomes compared to conventional methods. The main advantage of this research is its ability to detect the roundness of objects without requiring expensive specialized equipment. By using smartphones that many people already own, this application has the potential to be applied in various industries and applications that require quick and accurate roundness measurements. Overall, this research successfully developed an innovative method to detect round objects in real-time based on the Android platform. This method has the potential to reduce the cost and complexity of roundness measurement, offering an alternative that is more accessible and easier to implement in various contexts.